Field report PAC 671: Foo Boong Fong Co. / Amrul Shilmi Amir - Amir, Amrul Shilmi (Universiti Teknologi MARA, Terengganu, 2024)
Foo Boong Fong Company was founded in 1963 by Dato' Foo Boon Fong, a chartered accountant, with the intention of delivering exceptionally high-quality financial services to individuals and businesses in the neighborhood. Foo Boon Fong Company began as a little practice in Kuantan, Pahang, and over the course of several years, it has established a successful expansion of its services to other regions, including Kemaman and Mentakab. The company had grown to have a group of very skilled workers, each with their own area of expertise in accounting, taxes, and business advice. One of the most important factors that contributed to the company's expansion was its dedication to staying ahead of the trends in the business and embracing emerging technology.